Redescription of the Indo-West Pacific scorpionfish (Scorpaenidae), Neomerinthe erostris (Alcock 1896), a senior synonym of Scorpaena gibbifrons Fowler 1938, N. rotunda Chen 1981, and N. bathyperimensis Zajonz & Klausewitz 2002 - Motomura, Hiroyuki; Causse, Romain; Béarez, Philippe; Mishra, Subhrendu Sekhar (Zootaxa, 2015)
The Indo-West Pacific species, Neomerinthe erostris (Alcock 1896), originally described as Scorpaena erostris, is redescribed as a senior synonym of Scorpaena gibbifrons Fowler 1938, N. rotunda Chen 1981, and N. bathyperimensis Zajonz & Klausewitz 2002. Although the latter three nominal species have been regarded as valid species and N. erostris has not been reported since 1898, examinations of type specimens of the four nominal species revealed that they represent a single species. A lectotype of Scorpaena erostris is herein designated. Neomerinthe erostris is characterized by having a distinct longitudinal ridge on the lateral surface of the maxilla and a strongly rounded dorsal profile of the head.